Response of fennel (Foeniculum vulgare) to irrigation and mulching - O P Sharma, G L Choudhary, P Choudhary, M Meena, L R Yadav, S S Yadav, (Journal of Spices and Aromatic Crops, 2014)
A field experiment was conducted to find out the effect of irrigation levels and mulching on performance of fennel. Results indicated that application of six irrigations significantly increased the plant height, number of branches plant-1, total chlorophyll content, dry matter accumulation per metre row length, number of umbels plant-1, umbellets umbel-1, seeds umbellet-1 as well as seed, stover and biological yield of fennel compared to four and five irrigations. However, it remained at par with seven irrigations. Results further revealed that application of straw mulch significantly increased number of branches plant-1, dry matter accumulation per metre row length, number of umbellets umbel-1 and yields (seed, stover and biological) over control, dust and plastic mulches. Plant height and number of umbels plant-1 increased significantly with straw mulch as compared to control and dust mulch, but remained at par with plastic mulch. However, in respect of number of seeds umbellet-1, straw, plastic and dust mulch gave similar results.